Fine Morphology of Antennal and Ovipositor Sensory Structures of the Gall Chestnut Wasp, Dryocosmus kuriphilus - Milos Sevarika; Marco Valerio Rossi Stacconi; Roberto Romani (Insects, 2021)
Dryocosmus kuriphilus is a gall-inducing insect, which can cause significant damage on plants of the genus Castanea Mill., 1754. Antennae and ovipositor are the main sensory organs involved in the location of suitable oviposition sites. Antennal sensilla are involved in the host plant location, while ovipositor sensilla assess the suitability of the ovipositional bud. On both organs, diverse sensillar organs are present. Here, the distribution and ultrastructural organization of the sensilla were investigated by scanning and transmission electron microscopy. The antennae of D. kuriphilus are filiform and composed of 14 antennomeres, with the distal flagellomere bearing the highest number of sensilla. On the antennae, 6 sensilla types were found; sensilla chaetica, campaniformia, coeloconica-I, coeloconica-II, trichoidea and placoidea. The sensilla placoidea and trichoidea were the most abundant types. On the external walls of the ovipositor, gustatory and mechanoreceptive sensilla were observed. Internally, the egg channel hosted two additional sensory structures. The putative functional role of each sensilla in the context of insect’s ecology is discussed as well as the ovipositional mechanism used by this insect.